Deteksi dan Identifikasi Molekuler Kapang Berpotensi sebagai Penghasil Patulin pada Buah Tropis - Ratih Paramastuti; Winiati Pudji Rahayu; Siti Nurjanah (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2023)
Production and export of tropical fruits in Indonesia have an increasing trend every year. The important factor in the production and export of fruits is food safety. One of the contaminants that may be found in fruits is mycotoxin, especially patulin. Patulin mainly found in fruits such as apple, orange, grape, and pear. This study aimed to detect molds from tropical fruits and to identify potentially patulin-producing molds. Detection of potentially patulin-producing molds obtained from tropical fruits was carried out using the isoepoxydon dehydrogenase (idh) gene. Species identification was carried out using internal transcribed spacer (ITS) region. The mold isolate sequences of ITS rDNA region were analyzed for their homology using both BLAST search and phylogenetic tree. A total of 26 molds were isolated from four types of fruit (malang apple, ambon banana, medan orange, and avocado) obtained from five different places in Bogor including fruit stalls, traditional markets, and supermarkets. The positive results of idh gene were mold isolates that have an amplicon at 620 bp. The result showed that 5 of 26 (19,2%) isolates were positive for idh gene, namely A11, A34, A43, A51 and B23. The positive isolates for idh gene were identified as Aspergillus aculeatus, Aspergillus niger, Cladosporium anthropophilum, Cladosporium tenuissimum, and Talaromyces verruculosus.